REINTERPRETATION MEANING OF QIWAMA IN SURAH AN-NISA'VERSE 34 PERSPECTIVE HERMENEUTICS OF KHALED M. ABOU EL-FADL (International Conference on Social and Islamic Studies, 2022)
This study aims to find a new understanding and reinterpret the meaning of Qiwamah in the Qur'an Surah an-Nisa' verse 34. This reinterpretation needs to be done considering that there are some understandings from commentators who understand and provide an understanding of the meaning of Qiwamah as a guardian, leader, protector, Etc. This kind of understanding departs from the textual framework of thinking in the verses of the Qur'an. This interpretation model finally emerges in understanding and practice in the community where men or husbands in the household feel they have a higher position than women or wives. As a result, in the end, the man or husband tends to be authoritarian in establishing a household relationship because they feel they have legitimacy from the textual interpretation model. This article will review the meaning of Qiwamah through the negotiable hermeneutic approach of Khaled M. Abou el-Fadl to present a new understanding that is more humanistic and eliminates the excess power of men and their arbitrary attitude towards women. This research concludes that the meaning of Qiwamah, understood by some scholars of the interpretation, needs to be re-understood. One of the efforts to give birth to this new meaning is interpretation through the negotiable hermeneutic approach of Khaled M. Abou el-Fadl, which pays great attention to social problems that develop in Islamic society and the values ​​of justice and equality between men and women. The method used in this research is descriptive analysis.